Sistem Pakar Diagnosa Penyakit Pencernaan Menggunakan Metode Case Based Reasoning (CBR) Berbasis Web - Arfian Jumintar Sitorus; Jhonson Efendi Hutagalung; Ari Dermawan (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The main factors causing digestive disorders are food that is not good in terms of hygiene and health, nutritional balance, improper diet, infection, and abnormalities in the digestive organs so that they will contract several digestive diseases such as appendicitis, ulcers, stomach ulcers, hepatitis. , diarrhea and constipation. Early treatment is needed before consulting specifically with a digestive disease specialist before the disease is severe. In this case, it is necessary to have a system that can replace specialist doctors in diagnosing early symptoms of digestive diseases considering the high cost of consulting a doctor. This diagnostic expert system is very much needed in diagnosing early symptoms of the causes of digestive diseases. The application of the system is equipped with a Case Based Reasoning that solves new cases based on reasoning from old cases. The implementation has resulted in gastric cancer of 67.01% according to the symptoms selected by the patient, then the system also provides treatment advice, and provides information on the handling or treatment of gastric cancer, so that with this application it can help doctors in diagnosing the disease quickly.